PROTEASE FROM Styrax paralleloneurum LEAVES AND ITS THROMBOLYTIC ACTIVITY ASSAY - Sinaga, Ester Rosdiana; Martgrita, Merry Meryam; Kembaren, Roga Florida (Berita Biologi, 2025)
Thrombotic disease is one of the leading causes of death worldwide and enzymatic thrombolytic therapy remains the best way to achieve recanalization. Enzymatic thrombolytic agents used today have undesirable side effects, and some are expensive. Research for herbal protease enzymes was conducted because plant drugs are known to be safer. This study aimed to obtain protease enzymes from frankincense leaves and to test their thrombolytic activity. Enzyme concentration was determined by the Bradford method, and the results showed that the highest enzyme concentration was 1.6812 g/μL at 40% ammonium sulfate fraction. A quantitative assay of protease activity using Folin & Ciocalteu's phenol reagent and casein as substrate showed that 1.2609 mg of enzyme hydrolyzed 32.5 mg of casein and released 0.0980 mg of L-tyrosine. The fibrinogenolytic activity of protease against human fibrinogen tested by SDS-PAGE showed that the protease could hydrolyze fibrinogen γ-chain within 0 minutes and β-chain within 60 minutes, while α-chain could not be hydrolyzed until 720 minutes. The inhibitor effect assay showed that the protease was a serine protease. This study concluded that the protease enzyme from frankincense leaves has the potential to be used as a thrombolytic agent.